Reproducibility of isokinetic strength assessment of knee muscle actions in adult athletes: Torques and antagonist-agonist ratios derived at the same angle position - Duarte, João P. (2018)
The current study aimed to examine the reliability of the conventional and functional ratios derived from peak torques (PTs) and those obtained from the combination of knee flexors torque at the angle of knee extensors PT. Twenty-six male athletes (mean of 24.0±0.7 years) from different sports completed a test-to-test variation in isokinetic strength (Biodex, System 3) within a period of one week. Anthropometry and body composition assessed by Dual Energy X-ray Absorptiometry were also measured. The proposed isokinetic strength ratio measurements appeared to be highly reliable: conventional ratio at PT angle (intra-class correlation, ICC = 0.98; 95% confidence interval; 95%CI: 0.95 to 0.99); functional extension ratio at PT angle (ICC = 0.98; 95%CI: 0.96 to 0.99); and, functional flexion ratio at PT angle (ICC = 0.95; 95%CI: 0.89 to 0.98). Technical error of measurement (TEM) and associated percentage of the coefficient of variation (%CV) were as follows: conventional ratio at PT angle (TEM = 0.02; %CV = 4.1); functional extension ratio at PT angle (TEM = 0.02; %CV = 3.8); and, functional flexion ratio at PT angle (TEM = 0.03; %CV = 3.6). The current study demonstrated that the traditional and new obtained simple and combined isokinetic indicators seem highly reliable to assess muscle strength and function in adult male athletes. A single testing session seems to be sufficiently to obtain these isokinetic strength indicators.